Exploring the Indonesian EFL Students' Reading Anxiety and Attitude Before and After Covid-19 Pandemic - Iftanti, Erna (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2023)
The shifting mode of teaching reading comprehension from offline through online due to Covid 19 pandemic has changed the EFL students’ anxiety and attitude of reading. This paper is then aimed at revealing their anxiety and attitude of reading and the implication towards their reading performance. This study was done through distributing online questionnaire to seventy-five students of an English Department at a state Islamic University in Tulungagung East Java Indonesia, who attended reading course through online mode dan had ever joined offline reading comprehension class. The online survey was carried out from Mei -June 2021 when the pandemic was at its peak. The collected data which were qualitatively analysed and interpreted exposed three important points. Firstly, the pandemic that leads to physical and social distancing is believed to be able to reduce anxiety among the EFL undergraduate students when they are reading English. It is also believed to improve their positive attitude toward reading English, even though reading is not anymore perceived as their hobby. Moreover, their reading anxiety and attitude after the pandemic implicates to reducing their performance of reading for some conditions, i.e., the increasing number of school tasks, the time limitation, boredom, and the decreasing focus of online reading. This research results are pedagogically implemented to build positive attitude and reduce anxiety in online or offline reading.